2021
DOI: 10.1038/s41370-021-00371-z
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide exposures in wildland firefighters in the United States and targets for exposure reduction

Abstract: Aim 1 -Review of the Health Effects of Wildland Fire Smoke on Wildland Firefighters and the PublicReview the existing peer-reviewed literature from five major databases to identify smoke components that present the highest health hazard potential, the mechanisms of toxicity, and review epidemiological studies for health effects to identify the current gap in knowledge on the health impacts of wildland fire smoke exposure for firefighters and the public.Aim 2 -Smoke Exposure Among Wildland Firefighters Examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 96 publications
(158 reference statements)
0
6
0
Order By: Relevance
“…5 In addition to PM 4 , the NTDP field research team collected 1-min breathing zone carbon monoxide measurements through real-time dosimeters on wildland firefighter study participants during this field study. 36 CO mean concentrations exceeded the National Wildfire Coordinating Group's occupational exposure limit of 16 ppm on ∼5% of samples collected. This study also found that WFF perception of smoke exposure was a strong predictor of measured CO exposure.…”
Section: ■ Results and Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…5 In addition to PM 4 , the NTDP field research team collected 1-min breathing zone carbon monoxide measurements through real-time dosimeters on wildland firefighter study participants during this field study. 36 CO mean concentrations exceeded the National Wildfire Coordinating Group's occupational exposure limit of 16 ppm on ∼5% of samples collected. This study also found that WFF perception of smoke exposure was a strong predictor of measured CO exposure.…”
Section: ■ Results and Discussionmentioning
confidence: 83%
“…Exposure to PM from smoke is one of many hazardous air contaminants inhaled by wildland firefighters . In addition to PM 4 , the NTDP field research team collected 1-min breathing zone carbon monoxide measurements through real-time dosimeters on wildland firefighter study participants during this field study . CO mean concentrations exceeded the National Wildfire Coordinating Group’s occupational exposure limit of 16 ppm on ∼5% of samples collected.…”
Section: Resultsmentioning
confidence: 99%
“…The workshop recommended multidisciplinary research, policy development, and communication to address hazards for those managing and fighting wildland fires as well as the general public. Semmens et al (2021) identified specific wildland firefighter tasks related to direct suppression that could be targets for intervention aimed at wildland firefighters’ perception of smoke exposure and minimizing smoke exposure.…”
Section: Results: Occupational Health Hazards and Effects Related To ...mentioning
confidence: 99%
“…For this reason, carbon monoxide inhalation is a serious health hazard for firefighters (Navarro, 2020). Fire smoke can enter the lungs, where it absorbs into the blood and reduces oxygen delivery to vital organs (Reinhardt & Ottmar, 2004;Semmens et al, 2021).…”
Section: Wildfire and Human Healthmentioning
confidence: 99%